Modelo alométrico para estimar altura comercial y total de especies maderables en bosque de terraza alta, distrito de Urarinas, Loreto – 2025 - Palacios Nuñez, Flavio Anthony (2025)
The research was conducted in a high terrace ecosystem belonging to the Intermediate Forest Management Plan (PMFI) of the native community of San Juan de Abejaico, in the district of Urarinas, Loreto region. The objective was to evaluate the effectiveness of allometric models to estimate the commercial and total height of timber species. In Plot 1, 239 individuals of 13 species were recorded, while Plot 2 presented 148 individuals grouped in 7 species. Fabaceae was the dominant family, with Copaifera paupera and Parkia nitida standing out. In the canopy, Ceiba pentandra was the most representative species and Capirona decorticans predominated in early stages of succession, reflecting a recovering forest conditioned by edaphic factors. The analysis between diameter at breast height (DBH) and total height showed an increasing relationship: in Plot 1, trees with 50 cm of DBH reached 22.78 m and with 190 cm they reached 28.00 m. In Plot 2, height increased from 24.88 m to 27.50 m between diameters of 50 and 180 cm. In contrast, the commercial height showed greater dispersion, with maximums of 19.00 m (P1) and 17.50 m (P2). The cubic models offered a better fit: in Plot 1, R² = 0.694 (commercial height) and R² = 0.905 (total height); in Plot 2, R² = 0.551 and 0.675, respectively. This rules out the hypothesis of a linear relationship, demonstrating the greater predictive capacity of the cubic models.